Strengthening P3 Through Learning Models Project Based - Rejekiningsing, Triana; Ariana, Yudi; Triyanto, Triyanto; Hartanto, Rima Vien Permata; Gunawati, Dewi; Suryono, Hassan; Noventari, Widya (Jurnal Abdimas, 2023)
Community Service Activities with the aim of strengthening the Pancasila Student Profile through project-based learning, for teacher partners in the PPKn PPKn High School Subject Teacher Consultation (MGMP) Boyolali Regency. Community service is carried out by covering three stages, namely: planning, implementation, and evaluation. The planning stage is carried out in collaboration with the management of the SMA PPKn MGMP in Boyolali Regency, to share perceptions about Community Service activities and technical implementation. The implementation stage is carried out by a Workshop on strengthening the Pancasila Student Profile, and Assistance in developing project-based learning model mastery. Evaluation stage. carried out after the completion of the activity and the overall evaluation of the activity, and the sustainability of the activity by making the MGMP PPKn SMA in Boyolali Regency a fostered partner. Project citizen learning is an alternative solution in shaping the profile of Pancasila students. Through Project Citizen learning, students have the ability to collaborate and think critically, besides that they can become Indonesian citizens and citizens of the world who are responsible and actively contribute.